LESSON STUDY FOR INCREASING STUDENTS' ABILITY IN TEACHING PRACTICE - Fitri Handayani (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
Teaching practice is one of compulsory subject to be taken by English Department students of Universitas Mahaputra Muhammad Yamin Solok. This subject provides an opportunity for the students to apply their skill and knowtledge that they gained during their study in the real classroom environment. During this teaching practice, the students will be exposed to the real environment ofteaching process and its challenge in the field of education. As a beginner, doing teaching practice is not as easy as to be done by the students. A lot of challenges and complexities are found by the students during teaching practice. Those involve preparing lesson plan, developing good ilassroom management, preparing materials'and media, and participating in non-teaching activity. Lesson study is a good way to help students in doing teaching practice. Basically, it is a method of professional development carried out by teacheis in their own schools, with their own students and colleagues, in their own classroom to improve quality of teaching and learning. The teachers work collaboratively to plan. teach. observe and analyze lessons. Applying lesson study will be beneficial for teaching practice students in guiding them about the.way to teach English effectively. This paper will talk about the use of lesson study with the expectation to promote students' ability in teaching practice.